1987
DOI: 10.1016/0266-7681_87_90014-3
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Bone Graft Pedicled on the Volar Carpal Artery for Non-Union of the Scaphoid.

Abstract: A bone graft, taken from the medial part of the radial epiphysis can be pedicled on the radial branch of the volar carpal arch, freed back to its origin. The graft can be transferred into the proximal row of the carpus to fill up a loss of bony substance or to provide vascularised bone. This permits the treatment of chronic pseud-arthrosis of the scaphoid where a Matti-Russe operation has failed. In the first three cases operated upon, favourable results have been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…42 These VBGs are useful for treating scaphoid nonunion 42 43 44 45 and Kienböck's disease. 43 46 Kuhlmann et al 42 first reported results using volar distal radius VBGs. These grafts are elevated from the volar and ulnar distal radius, and one incision can be used for harvest and transfer.…”
Section: Volar Distal Radius Pedicled Vbgsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 These VBGs are useful for treating scaphoid nonunion 42 43 44 45 and Kienböck's disease. 43 46 Kuhlmann et al 42 first reported results using volar distal radius VBGs. These grafts are elevated from the volar and ulnar distal radius, and one incision can be used for harvest and transfer.…”
Section: Volar Distal Radius Pedicled Vbgsmentioning
confidence: 99%
“…Volar distal radius VBGs are the preferred pedicled VBGs for the treatment of humpback deformities of the scaphoid as they tend to be better in restoring normal carpal geometry, specifically the intrascaphoid angle, scapholunate angle, and carpal height ratio. 26,42 Relative contraindications to these VBGs are prior trauma and/or surgeries to the volar distal radius region. 26 Reported outcomes from pedicled volar distal radius VBG have been positive.…”
Section: Volar Distal Radius Pedicled Vbgs Volar Carpal Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…This flap is particularly well suited for conservative reconstruction of small bone defects and nonunion, such as in the wrist, with an excellent bone union rate [23,24]. It allows larger bone defects to be filled than with Zaidemberg's vascularized radial graft [25] and the vascularized bone graft pedicle on the volar carpal artery described by Kuhlmann et al [26].…”
Section: Advantages Of Skin Paddle On the Mft Flapmentioning
confidence: 99%
“…Se han propuesto diversos tipos de IOV para el tratamiento de la pseudoartrosis del escafoides y, aunque ha sido descrita la transferencia microvascular libre de hueso de cresta iliaca 30 , la mayoría de autores utilizan injertos pediculados. El pedículo vascular puede obtenerse de la inserción del pronador cuadrado [31][32][33][34] , de la arteria carpiana palmar [35][36][37] , de la arteria cubital 38 , de la arteria intermetacarpiana del primer o segundo espacio dorsal [39][40][41][42] , o de la primera arteria septal del dorso del radio [43][44] .…”
Section: Utilidad De Los Injertos óSeos Vascularizadosunclassified